Winter is coming: nightmares and sleep problems during seasonal affective disorder - Nils Sandman; Ilona Merikanto; Hanna Määttänen; Katja Valli; Erkki Kronholm; Tiina Laatikainen; Timo Partonen; Tiina Paunio (John Wiley & Sons Ltd, 2022)
Sleep problems, especially nightmares and insomnia, often accompany
depression. This study investigated how nightmares, symptoms of
insomnia, chronotype and sleep duration associate with seasonal
affective disorder, a special form of depression. Additionally, it was
noted how latitude, a proxy for photoperiod, and characteristics of the
place of residence affect the prevalence of seasonal affective disorder
and sleep problems. To study these questions, data from FINRISK 2012
study were used. FINRISK 2012 consists of a random population sample
of Finnish adults aged 25–74 years (n = 4905) collected during winter
from Finnish urban and rural areas spanning the latitudes of 60°N to
66°N. The Seasonal Pattern Assessment Questionnaire was used to
assess symptoms of seasonal affective disorder. Participants with
symptoms of seasonal affective disorder had significantly increased
odds of experiencing frequent nightmares and symptoms of insomnia,
and they were more often evening chronotypes. Associations between
latitude, population size and urbanicity with seasonal affective disorder
symptoms and sleep disturbances were generally not significant,
although participants living in areas bordering urban centres had less
sleep problems than participants from other regions. These data show
that the prevalence of seasonal affective disorder was not affected by
latitude.